Administration of a Combined Probiotic Feed Containing Streptococcus thermophilus and Bacillus coagulans on Growth Performance and Molting Frequency in Black Tiger Shrimp (Penaeus monodon Fab.) - Alifia, Difa; Putra, Dedi Fazriansyah; Nurfadillah; Suratno (College of Vocational Studies, Bogor Agricultural University, 2025)
The black tiger shrimp (Penaeus monodon Fab.) is one of Indonesia’s leading aquaculture commodities; however, its production has declined due to various factors affecting growth, such as feed quality and environmental conditions. This study aimed to evaluate the effect of incorporating the probiotics Streptococcus thermophilus and Bacillus coagulans to shrimp feed on growth performance, feed efficiency, and molting frequency of black tiger shrimp. The study was conducted using a completely randomized design (CRD) with six treatments: one control (no probiotic addition) and five probiotic treatments at a dose of 15 mL/kg of feed, these treatments were as follows: A (control), B (100% S. thermophilus), C (100% B. coagulans), D (50% S. thermophilus and 50% B. coagulans), E (75% S. thermophilus and 25% B. coagulans), and F (25% S. thermophilus and 75% B. coagulans). Measured parameters included absolute body length, absolute body weight, feed conversion ratio (FCR), specific growth rate (SGR), survival rate (SR), feed efficiency (FE), and molting frequency. The results indicated that treatment with B. coagulans (Treatment C) had a significant effect on absolute weight, specific growth rate, and survival rate, but no significant effect on FCR, FE, and molting frequency. In conclusion, the addition of B. coagulans to shrimp feed shows potential in enhancing growth performance in Penaeus monodon.